Qur’anic Learning In The Digital Era: A Study On Digital Applications And Their Impact - Ida Faridatul Hasanah; Uswatun Hasanah; Minhah Makhzuniyah; Aminah Nur Kauthar Binti Zawawi (Universitas Trunodjoyo Madura, 2025)
The utilization of digital technology has significantly transformed the way Muslims study the Qur'an. Digital Qur'an applications, online platforms, and artificial intelligence (AI) provide easier and faster access to religious texts, including Qur'anic exegesis and studies. However, concerns arise regarding the potential impact of these technologies on the depth of religious understanding, especially in preserving the spiritual and traditional aspects of Qur'anic studies. This study aims to explore the optimal use of digital technology in Qur'anic studies and examine the opportunities and challenges with a focus on digital applications. A qualitative approach was employed using library research, drawing from literature sources such as books, academic journals, articles, and relevant research reports. Findings reveal that digital technology offers numerous conveniences, such as broad, interactive, and flexible access. However, challenges like potential misuse of shallow interpretations, dependence on algorithms, and declining quality of teacher-student interactions pose significant concerns. Thus, the application of digital technology in Qur'anic studies should adopt a wise approach, adhering to the principles of Islamic scholarship and spirituality. Additionally, digital literacy and collaboration between religious scholars and technology developers are essential to ensure that digital applications and platforms genuinely support a profound and contextual understanding of the Qur'an, assisting users in filtering information from credible sources while avoiding the spread of inappropriate content.